2020
DOI: 10.1073/pnas.2013686117
|View full text |Cite
|
Sign up to set email alerts
|

Two populations of self-maintaining monocyte-independent macrophages exist in adult epididymis and testis

Abstract: Macrophages are the principal immune cells of the epididymis and testis, but their origins, heterogeneity, development, and maintenance are not well understood. Here, we describe distinct populations of epididymal and testicular macrophages that display an organ-specific cellular identity. Combining in vivo fate-mapping, chimeric and parabiotic mouse models with in-depth cellular analyses, we found that CD64hiMHCIIlo and CD64loMHCIIhi macrophage populations of epididymis and testis arise sequentially from yolk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 63 publications
(87 reference statements)
8
100
1
2
Order By: Relevance
“…According to the morphology and localization, human testicular macrophages could be classified into interstitial and peritubular macrophages; but no marker has been found to distinguish both types ( 86 ). Unlike in humans, mouse testicular interstitial and peritubular macrophages were characterized by CD64 hi MHCII lo and CD64 lo MHCII hi , respectively ( 87 , 88 ). Once established in the niche, except the empty niche, these macrophages self-maintain for long periods of time without replenishment from blood monocytes in the steady condition ( 88 ).…”
Section: Possible Contribution Of Metabolism Of Immune Cells To Male Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the morphology and localization, human testicular macrophages could be classified into interstitial and peritubular macrophages; but no marker has been found to distinguish both types ( 86 ). Unlike in humans, mouse testicular interstitial and peritubular macrophages were characterized by CD64 hi MHCII lo and CD64 lo MHCII hi , respectively ( 87 , 88 ). Once established in the niche, except the empty niche, these macrophages self-maintain for long periods of time without replenishment from blood monocytes in the steady condition ( 88 ).…”
Section: Possible Contribution Of Metabolism Of Immune Cells To Male Reproductionmentioning
confidence: 99%
“…Unlike in humans, mouse testicular interstitial and peritubular macrophages were characterized by CD64 hi MHCII lo and CD64 lo MHCII hi , respectively ( 87 , 88 ). Once established in the niche, except the empty niche, these macrophages self-maintain for long periods of time without replenishment from blood monocytes in the steady condition ( 88 ). Interstitial macrophages closely contact with Leydig cells, which might contribute to facilitate testosterone.…”
Section: Possible Contribution Of Metabolism Of Immune Cells To Male Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the hormonal imbalances in the testes of these mice likely had initiated changes in the macrophage populations, resulting in the acquisition of this unique population. Whether the changes involve recruitment of a new macrophage population, as recently suggested to occur after radiation or infection [ 19 ] and whether or to which degree the factors of the local environment contribute to these changes [ 15 ], remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Already at birth, a testicular compartment, i.e., the interstitial space is occupied by CD206 + MHC II - macrophages, whereas CD206 - MHC II + ones surround the seminiferous tubules. Furthermore, a new study showed that after radiation or during infection, bone marrow-derived circulating monocytes are recruited to the testis and give rise to inflammatory macrophages which then promote tissue damage [ 19 ]. Hence, testicular macrophages can be heterogeneous.…”
Section: Introductionmentioning
confidence: 99%